2012
DOI: 10.1111/j.1468-3083.2012.04467.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset alopecia areata: A retrospective study of 73 patients from Taiwan

Abstract: Late-onset AA is characterized by marked female predominance and milder disease activity with increasing age. The link to cancer in the old age remains to be determined. The influence of aging on the pathogenesis and prognosis of AA deserves further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 23 publications
7
36
3
2
Order By: Relevance
“…Seven cross-sectional studies reported that the prevalence of both AA and personal history of atopy in adults ranges from 22 to 38% when confounding variables are considered [2, 13-18]. Results regarding the association of AA and atopy in adults is controversial, with some studies suggesting that patients with atopy also present more frequently with severe AA [2, 16] and other studies reporting a lack of an association between patients with AA and a personal history of atopy [13, 19].…”
Section: Resultsmentioning
confidence: 99%
“…Seven cross-sectional studies reported that the prevalence of both AA and personal history of atopy in adults ranges from 22 to 38% when confounding variables are considered [2, 13-18]. Results regarding the association of AA and atopy in adults is controversial, with some studies suggesting that patients with atopy also present more frequently with severe AA [2, 16] and other studies reporting a lack of an association between patients with AA and a personal history of atopy [13, 19].…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al 15 reported that of patients in whom AA first developed before the age of 40 years, 36.5% presented with extensive AA, whereas extensive AA was only seen in 5.5% of the patients in whom AA was first observed after the age of 40 years (P < 0.05). Moreover, Wu et al 16 reported that among 73 AA patients, those in whom AA first occurred at the age of 50 years and older presented with less severe conditions, suggesting that graying hair may help to prevent AA. Our study included patients with intractable AU who were aged 40 years or older both at the onset of the condition and the start of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the patients was 45.7 AE 16.9 years (range, 24-66) and the mean disease duration was 9.3 AE 8.1 years (range, 1-22). The treatments administrated to the patients included topical steroids (mean, 25 months; range, 3-60), infrared therapy (mean, 15.8 months; range, 9-30), topical immunotherapy (mean, 15.4 months; range, 7-29), corticosteroid pulse therapy and cryotherapy (mean, 11 months; range, [6][7][8][9][10][11][12][13][14][15][16]. In all cases, hair loss that extended beyond the scalp was used to confirm the diagnosis of AU.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, rapid development of AA has been previously reported in cases of AA manifesting as a paraneoplastic phenomenon [12]. Furthermore, in a cohort of 73 patients with first onset of AA at the age of 50 years and above, 8% had a history of malignancy before or after the onset of AA [11]. Taken together, these reports raise the question of whether or not patients older than 40 who present for the first time with a rapidly progressing AA should be screened for malignancy with proper blood and imaging tests.…”
Section: Discussionmentioning
confidence: 99%
“…It should be taken into consideration that the severity of AA when first appearing in adults is usually mild in nature, and more than half of the adult patients with AA have less than 10% involvement of the scalp [11]. Indeed, rapid development of AA has been previously reported in cases of AA manifesting as a paraneoplastic phenomenon [12].…”
Section: Discussionmentioning
confidence: 99%